Pengaruh Aktivitas Antropogenik terhadap Keragaman Genetik Rhizophora mucronata Lamk. di Hutan Mangrove Secanggang, Sumatera Utara (Effect of Anthropogenic Activities on Genetic Variation of Rhizophora mucronata Lamk. in Secanggang Mangrove Forest, North - Mohammad Basyuni; Hamzah Hamzah; Suci Rahayu; Ulfah J. Siregar (FORESTA, 2012)
Deforestation and fragmentation of mangrove forests in Indonesia are widespread that resulted in losing biodiversity including genetic variation. Rhizophora mucronata Lamk. is a common mangrove species in Secanggang, Langkat, North Sumatra and have been degrading due to anthropogenic disturbance. The aim of this study is to determine the genetic variation in natural population of R. mucronata in Secanggang, North Sumatra using isozyme markers. From five enzymes systems used namely aspartate aminotransferase (AAT), alcohol dehydrogenase (ADH), esterase (EST), malate dehydrogenase (MDH), and peroksidase (PER); eleven loci was found and five polymorphic loci were detected.The estimate value of genetic variation parameters i.e. observed and expected heterozygosity, average alel per loci, and average polymorphic (95% criteria) were 0.1386, 0.1724, 1.5455, and 45.45 % respectively.The low genetic variation of R. mucronata found in this study suggested that genetic variation may be influenced by anthropogenic activities such as illegal logging, conversion into shrimp pond and agricultural farm.Keywords: Anthropogenic, genetic variation, isozyme, mangrove, Rhizophora mucronata